2017
DOI: 10.1136/vr.104466
|View full text |Cite
|
Sign up to set email alerts
|

Field study on the safety and efficacy of intradermal versus intramuscular vaccination against Mycoplasma hyopneumoniae

Abstract: The present study compares the safety and efficacy of a needle-free, intradermal vaccine to an intramuscular one. 420 piglets (21+3 days of age) were randomly assigned to two vaccination groups (intradermal vaccination V1 (n=138), intramuscular vaccination V2 (n=144)) and one unvaccinated control group (CG, n=138). As safety parameters clinical observations, local injection site reactions (ISR) and rectal temperatures were assessed. Average daily weight gain (ADWG) and pneumonic lung lesions (LL) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…Overall, the ISR occasionally observed in all IM vaccinated groups and at the IM injection site of group Lipo_DDA:TDB were mild and resolved quickly. Transient redness and swelling at vaccination sites were also reported in other M. hyopneumoniae vaccination studies (53–55). Such local reactions often occur after parenteral administration of adjuvanted vaccines and are tolerated in terms of safety (52).…”
Section: Discussionsupporting
confidence: 77%
“…Overall, the ISR occasionally observed in all IM vaccinated groups and at the IM injection site of group Lipo_DDA:TDB were mild and resolved quickly. Transient redness and swelling at vaccination sites were also reported in other M. hyopneumoniae vaccination studies (53–55). Such local reactions often occur after parenteral administration of adjuvanted vaccines and are tolerated in terms of safety (52).…”
Section: Discussionsupporting
confidence: 77%
“…Many other researchers found that Mhp commercial vaccines are not effective in mouse immunization experiments [9,10,26,27,28]. However, similar commercial vaccines have been proved to be safe and effective in experimental or field conditions of piglet immunization [7,29,30,31]. The types of vaccines used in these studies are inactivated or attenuated vaccines, which is similar to the inactivated Mhp vaccine used in this study, while the PCV2 vaccine used in this study is a protein-type vaccine, so it works well in both mouse and pig experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Within the wide range of vaccine products available, all of them are for intramuscular administration, except one vaccine for intradermal application. Studies by Martelli et al, [12], Tassis et al, [13], and Beffort et al, [14] have demonstrated, not only the greater e cacy of this product against other vaccines for intramuscular use (in terms of average daily weight gain (ADWG), reduction of clinical signs and lung lesions) but also an increase in the levels of local protection at the pulmonary level with respect to some vaccines, measured in the form of IgA and levels of Il-10.…”
Section: Introductionmentioning
confidence: 95%